Neurorestoration After Traumatic Brain Injury: Innovative Therapies for Restoring Function and Quality of Life - Susilawati, Ni Nyoman Ayu; Putri, Siti Noururrifqiyati Juna; Prayitno, Oktavianus; Panjaitan, Melisa Parida Djayanty (Jurnal Biologi Tropis, 2025)
Traumatic brain injury (TBI) is a major cause of death and disability globally, with 50 million cases annually and increasing emergency department visits. Despite advances in management, such as decompressive craniotomy and hypothermia, severe TBI still leads to poor outcomes in about 50% of patients, emphasizing the limited effectiveness of conventional therapies. This has led to the development of neurorestorative approaches to enhance brain function and recovery after injury. Literature was sourced from Google Scholar, ScienceDirect, and PubMed, with studies from 2015–2025, in English or Indonesian, and involving human or animal subjects. Neurorestorative strategies include cellular therapies (e.g., mesenchymal stem cells), neurostimulation (invasive and non-invasive methods), pharmacological interventions (e.g., erythropoietin and statins), and supportive therapies (e.g., hyperbaric oxygen). Cellular therapy shows promise in promoting neurogenesis and recovery, though large-scale trials are needed. Neurostimulation has been shown to improve consciousness and neurological function in patients with chronic consciousness disorders, while pharmacological and supportive treatments present mixed results and require more research. Neurorestorative therapies offer hope for TBI recovery, but study limitations, including design and sample size, prevent generalization. Further research and large-scale randomized clinical trials are necessary to ensure safety, effectiveness, and optimal integration of neurorestorative modalities.